Simulasi Gelombang Di Pantai Bengkalis Dengan Menggunakan CADMAS-SURF - Defarian, Alvin; Sutikno, Sigit; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Bengkalis Coast has been attacked by abrassion process and needs to be restored as before with mangrove restoration. The purpose of this study is to analyze the characteristics of sea waves and to analyze the condition of the coast for conducive of mangrove restoration. The method used is wave simulation by some alternative cases which is processed using CADMAS-SURF. The area of study was focused in Selat Baru Coast, northern part of Bengkalis Island. The results show that Selat Baru coast has a significant wave height of1,396 m and a period of 5,572 seconds. Protected coastal areas of the breakwater is a conducive condition for mangrove restoration.Keyword: wave simulation, bengkalis coast, CADMAS-SURF